Neutral Red Film Augments Extracellular Electron Transfer Performed by Clostridium pasteurianum DSM 525 - Zani, Ana Clara Bonizol; de Souza, João Carlos [UNESP]; de Andrade, Adalgisa Rodrigues [UNESP]; Reginatto, Valeria (MDPI, 2024)
Extracellular electron transfer (EET) is key to the success of microbial fuel cells (MFCs). Clostridium sp. often occurs in MFC anode communities, but its ability to perform EET remains controversial. We have employed Clostridium pasteurianum DSM 525 as a biocatalyst in a glycerol-fed MFC, designated MFCDSM. We have also followed the EET of this biocatalyst in the presence of a mediator, namely soluble neutral red (NR), soluble methyl viologen (MV), neutral red film (FNR), or methyl viologen film (FMV). MFCDSM provided power and current densities (j) of 0.39 μW·cm−2 and 2.47 μA·cm−2, respectively, which evidenced that the biocatalyst performs direct electron transfer (DET). Introducing 150.0 µM NR or MV into the MFCDSM improved the current density by 7.0- and 3.7-fold (17.05 and 8.45 μA·cm−2), respectively. After 20 cyclic voltammetry (CV) cycles, the presence of FNR in the MFCDSM anodic chamber provided an almost twofold higher current density (30.76 µA·cm−2) compared to the presence of NR in the MFCDSM. Introducing MV or FMV into the MFCDSM anodic chamber gave practically the same current density after 10 CV cycles. The MFCDSM anodic electrode might interact with FMV weakly than with FNR, so FNR is more promising to enhance C. pasteurianum DSM 525 EET within MFCDSM.
Keywords: Clostridium pasteurianum DSM 525; glycerol; mediated electron transfer (MET); methyl viologen (MV); neutral red (NR)